Ultrastructural analysis of the root canal walls after preparation with two rotary nickel-titanium endodontic instruments - Claudio Poggio; Alberto Dagna; Marco Chiesa; Riccardo Beltrami; Marco Colombo (Wolters Kluwer Medknow Publications, 2014)
Background: Root canal preparation may produce a large quantity of smear layer that covers canal walls. Aims: The aim of this study was to evaluate by Scanning Electron Microscope (SEM) the root canal dentine after instrumentation with nickel-titanium rotary files, in order to evaluate the presence/absence of smear layer and the presence/absence of open tubules on the root canal walls at the coronal, middle, and apical third of each sample. Materials and Methods: A total of 20 single-rooted freshly extracted teeth were selected and divided into two groups. For each group, root canals were shaped with Mtwo and Revo-S instruments under irrigation with Sodium hypochlorite and 17% ethylenediaminetetraacetic acid. Specimens were fractured longitudinally and SEM analyzed at standard magnification of ×1000 and ×5000. The presence/absence of smear layer and the presence/absence of open tubules at the coronal, middle, and apical third of each canal were evaluated using a three-step scale for scores. Statistical Analysis Used: Numeric data were analyzed using the Kruskall-Wallis and Mann-Whitney U-Statistical tests and significance was pre-determined at P < 0.05. Results and Conclusions: This study did not reveal differences among the two groups. Mtwo and Revo-S showed no significant difference between them and both presented very low smear layer scores and open tubules scores, with no significant difference among coronal, middle, and apical third. Mtwo and Revo-S rotary instruments seem to be effective in removing smear layer from canal walls.